Determinants of postnatal checkup for newborns in Ethiopia: Further analysis of 2016 Ethiopia demographic and health survey - Abdu Seid; Mohammed Ahmed (BMC, 2020)
Abstract Background The absence of suitable care during the postpartum period might result in substantial ill-health and even the demise of newborns. So, identifying and intervening thus factors increase postnatal newborn care utilization thereby reducing neonatal mortality. Therefore, this study aimed to ascertain the determinants of the postnatal checkup of a newborn in Ethiopia. Method A cross-sectional study was accompanied using the 2016 Ethiopia Demographic and Health Survey (EDHS) data set. The samples were designated by employing a two-stage stratified cluster sampling technique. All statistical analysis were weighted in order to take into consideration complex survey design. Bivariate and multivariate logistic regression analysis was also carried out to examine the association between use of postnatal care of newborn and selected independent variables. Adjusted odds ratios (AOR) were used to state a statistically significant suggestion. Result A total of 7091 samples of the reproductive age of newborn mothers were included and analyzed. According to multivariate analysis, the odds of postnatal checkups of the newborn were 2.45 times higher among mothers who had 1-3 ANC visits and 3.42 times higher among mothers who had four and above visits than mother who did not have ANC visit. The odds of postnatal checkups of the newborn were 1.4 times higher among mothers who had access to media compared to their counterparts. Likewise, the odds of postnatal checkups of the newborn were 1.67 times higher among mothers who had delivered in a health facility than who delivered at home. Conclusions This study revealed that accessed media, being rich or middle in the wealth index category, having ANC visits, and institutional delivery was positively associated with the utilization of postnatal care checkup of the newborn. Therefore, information education and communication programs should perform a critical role in inspiring mother to take their newborns for postnatal checkup after birth.